2013
DOI: 10.1126/scisignal.2004431
|View full text |Cite
|
Sign up to set email alerts
|

The TNF Family Member 4-1BBL Sustains Inflammation by Interacting with TLR Signaling Components During Late-Phase Activation

Abstract: Activation of Toll-like receptor (TLR)-dependent signaling leads to the expression of genes that encode pro-inflammatory factors, such as tumor necrosis factor α (TNF-α), and this process is sustained for the duration of the inflammatory response. TLR-mediated inflammation, which occurs in two phases, depends on the TNF family member 4-1BB ligand (4-1BBL) to sustain TNF-α production during late-phase signaling. Here, we showed that Toll–interleukin-1 receptor (TIR) domain–containing adaptor protein (TIRAP) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 46 publications
0
25
0
Order By: Relevance
“…Findings from our study revealed that TRAF6 peptide inhibitor or siRNA knockdown (but not non-target RNA) alleviated or ablated LPS-induced contractile anomalies, apoptosis and Akt activation, indicating a role of TRAF6 in LPS-induced cell injury. Inhibition of TRAF6 using RNA silence or decoy peptides decreases tumor cell proliferation and promotes apoptosis [26, 27, 43] although insufficient information is available with regards to the role of TRAF6 in heart failure. Ubiquitination, an essential component of the ubiquitin-proteasome system (UPS), is a cell degradation machinery through which mammalian cells degrade and recycle macromolecules and organelles [44].…”
Section: Discussionmentioning
confidence: 99%
“…Findings from our study revealed that TRAF6 peptide inhibitor or siRNA knockdown (but not non-target RNA) alleviated or ablated LPS-induced contractile anomalies, apoptosis and Akt activation, indicating a role of TRAF6 in LPS-induced cell injury. Inhibition of TRAF6 using RNA silence or decoy peptides decreases tumor cell proliferation and promotes apoptosis [26, 27, 43] although insufficient information is available with regards to the role of TRAF6 in heart failure. Ubiquitination, an essential component of the ubiquitin-proteasome system (UPS), is a cell degradation machinery through which mammalian cells degrade and recycle macromolecules and organelles [44].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that 4-1BB/4-1BBL signaling is critical for the activation and survival of dendritic cells (29) and the conversion of monocytes into dendritic cells (30). Interesting in this context, it was shown that TLR signaling induces 4-1BBL expression on the surface of macrophages and the physical interaction of 4-1BBL with TLR-4 is necessary for sustained TNF production (31, 32). We did not observe synergy between MPL and SA-4-1BBL on bone marrow derived DCs for the induction of costimulatory molecules or elaboration of various proinflammatory cytokines (Table S2).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the early phase of TLR responses, this later phase controlled by 4‐1BBL does not induce the activation of NF‐κB pathway, while MAPKs, protein kinases, and transcription factors, such as CREB and C/EBP that play an essential role in sustaining expression of TNF. Specifically, we found that inhibition of the 4‐1BBL‐TIRAP interaction significantly reduced TNF production in macrophages in vitro and improved survival of mice in a model of endotoxin‐induced sepsis , suggesting that the 4‐1BBL‐mediated signaling may be a target of anti‐inflammation treatments.…”
Section: Introductionmentioning
confidence: 90%
“…Explaining this phenomenon, we showed that the TLR response induces the expression of 4‐1BBL during the early phase of macrophage activation and subsequently the newly expressed 4‐1BBL interacts with the TLRs to initiate a secondary late‐phase signaling response to sustain TNF expression . The TLR‐4‐1BBL complex interacts with an adaptor protein TIRAP and a kinase IRAK2, but not with MyD88 and TRIF, to activate a downstream signaling cascade that includes TRAF6‐TAK1‐TAB1 . Unlike the early phase of TLR responses, this later phase controlled by 4‐1BBL does not induce the activation of NF‐κB pathway, while MAPKs, protein kinases, and transcription factors, such as CREB and C/EBP that play an essential role in sustaining expression of TNF.…”
Section: Introductionmentioning
confidence: 99%